Perhitungan Faktor Beban Gaya Lingkungan untuk Analisa Struktur Anjungan Lepas Pantai dengan Metoda LRFD - Tawekal, Ricky L (Department of Civil Engineering, Diponegoro University, 2004)
Up to this moment, structural design of offshore platforms in Indonesia is carried out by using API RP2A standard which is originally used for Gulf of Mexico environment. This will result in an over designed structure since the environment in Indonesia is less severe compare to the environment in Gulf of Mexico. Therefore, the environmental load factors that specified in API RP2A LRFD should be reviewed and determined based on local environmental condition. In this paper, a model of 4-leg jacket structure is used to determine environmental load factor based on environmental condition at South East Sumatera Area. Structural analysis is carried out by using SACS (Structural Analysis Computer System) software. Keywords: load and resistance factor design, offshore structures, load factorPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3886[How to cite: Tawekal, R.L., 2004, Perhitungan Faktor Beban Gaya Lingkungan untuk Analisa Struktur Anjungan Lepas Pantai dengan Metoda LRFD, Jurnal Media Komunikasi Teknik Sipil, Volume 12, Nomor 3, pp. 12-26]